Cathepsin B-Responsive Liposomes for Controlled Anticancer Drug Delivery in Hep G2 Cells - Seulgi Lee; Su Jeong Song; Jeil Lee; Tai Hwan Ha; Joon Sig Choi (MDPI AG, 2020)
In recent decades, several types of anticancer drugs that inhibit cancer cell growth and cause cell death have been developed for chemotherapeutic application. However, these agents are usually associated with side effects resulting from nonspecific delivery, which may induce cytotoxicity in healthy cells. To reduce the nonspecific delivery issue, nanoparticles have been successfully used for the delivery of anticancer drugs to specific target sites. In this study, a functional polymeric lipid, PEG-GLFG-K(C16)2 (PEG-GLFG, polyethylene glycol-Gly-Leu-Phe-Gly-Lys(C16)2), was synthesized to enable controlled anticancer drug delivery using cathepsin B enzyme-responsive liposomes. The liposomes composed of PEG-GLFG/DOTAP (1,2-dioleoyl-3-trimethylammonium-propane (chloride salt))/DPPC (dipalmitoylphosphatidylcholine)/cholesterol were prepared and characterized at various ratios. The GLFG liposomes formed were stable liposomes and were degraded when acted upon by cathepsin B enzyme. Doxorubicin (Dox) loaded GLFG liposomes (GLFG/Dox) were observed to exert an effective anticancer effect on Hep G2 cells in vitro and inhibit cancer cell proliferation in a zebrafish model.